Live weight uniformity on the day-old chick of Indonesian local chickens - Saraswati, Yesita Vera; Mustofa, Fatmawati; Aprilianna Putri Zahara Nafsina Luvita Sari,; Sasongko, Heru; Ariyadi, Bambang; Maharani, Dyah (Penerbit Universiti Kebangsaan Malaysia, 2023)
The uniformity of live weight in the early stage (DOC) is an indicator applied to evaluate the quality of brooding, raising, and growth management. This study aims to compare the live weight uniformity of DOC in three local breeds as a parental group, namely Merawang A and B (n:196), Murung Panggang (n:157), and KUB (n:416), as well as in five groups of Bulaksumur (BS) for crossbred group, namely BS-1 (n:136), BS-2 (n:76), BS-3 (n:106), BS-5 (n:81), BS-6 (n:164). The live weight data of DOC was obtained in Gunungkidul Regency under similar management. The results show that the BS groups had higher live weight (31.9 g ± 3.1) compared to Merawang A (24 g ± 3.1), Murung Panggang (28.2 g ± 2.3), and KUB (28.1 g ± 2.8). Furthermore, the live weight uniformity on the BS DOC averaged 71% across all groups, with the highest uniformity being BS-3 (87%). Murung Panggang had a higher live weight uniformity (82%) compared to Merawang A and B (42%, 64%) and KUB (63%). The average coefficient variance was less than 10%, except for Merawang A and BS-2 with 13.09% and 11.35%, respectively. In conclusion, the DOC of the crossbred (BS) was more uniform than its parental groups. However, to distinguish the significantly different in the chicken live weight in early stage, further analysis needs to be conducted in the future.